(untitled) (Biological Sciences - PJSIR, 2019)
The experiment was conducted during winter season 2014-15 at Sindh Agriculture University Nursery, Tandojam, Pakistan. Five ornamental plants viz; ixora, chrysanthemum, vine, sunflower and jasmine were kept under observation. Collection was done once a week through in situ and sweep net methods. Data was collected by examining 10 randomly selected plants of each ornamental plant species. The collected specimens were brought in the laboratory and identified at species level. The results indicated that there were 24 insect species found active on the ornamental plant species during study period. However, aphid, shield bug, flower feeder, white ant, whitefly, red spider mite and mealy bug were found the most active on Ixora. Aphids, leaf miner, flower feeder, green grass hopper, midges, earwigs and whitefly were found associated with Chrysanthemum. Similarly, aphid, blister mite, mealy bug, midges, red mite and whitefly were found active on vine ornamental creeper. The insects found active on sunflower were aphids, butterfly, green grass hopper, hairy caterpillar, head borer, leaf hopper, midges, ground beetle, red spider mite and white ants. Jasmine plant harboured red spider mite, whitefly, jasmine bug, leaf hopper, white ant and green grass hopper. Among beneficial insects such as predators, pollinators and parasitoids, the green lacewing, honey bee, hoverfly, Trichogramma, praying mantis, zigzag beetle and Tachinid fly were the active insects on all ornamental plants kept under observation. Aphids were found frequently occurring on most of the ornamental plants.